2013
DOI: 10.1007/978-1-4614-1590-9_14
|View full text |Cite
|
Sign up to set email alerts
|

A Glimpsing Account of the Role of Temporal Fine Structure Information in Speech Recognition

Abstract: Many behavioral studies have reported a significant decrease in intelligibility when the temporal fine structure (TFS) of a sound mixture is replaced with noise or tones (i.e., vocoder processing). This finding has led to the conclusion that TFS information is critical for speech recognition in noise. How the normal -auditory system takes advantage of the original TFS, however, remains unclear. Three -experiments on the role of TFS in noise are described. All three experiments measured speech recognition in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Combined with the above evidence, this suggests that while TFS may enhance source segregation, it still appears to contribute to linguistic interference of segregated signals. This finding is significant regarding recent discussions related to the role of TFS for source segregation and linguistic processing (Apoux and Healy, 2013;Fogerty and Entwistle, 2015). …”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Combined with the above evidence, this suggests that while TFS may enhance source segregation, it still appears to contribute to linguistic interference of segregated signals. This finding is significant regarding recent discussions related to the role of TFS for source segregation and linguistic processing (Apoux and Healy, 2013;Fogerty and Entwistle, 2015). …”
Section: Discussionsupporting
confidence: 52%
“…Processing selectively preserved amplitude modulations (ENV) and degraded frequency modulations conveyed by the temporal fine structure (TFS). This method has the advantage of limiting cues provided by the acoustic TFS while avoiding confounds of vocoder processing that use the same carrier for both target and competing stimuli (Apoux and Healy, 2013). First, the speech signal was combined with noise matching the same power spectrum of the target speech at 11 dB signal-to-noise ratio (SNR).…”
Section: Envelope Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise indicated, we will regard "E" and "TFS" as the acoustic E and acoustic TFS specifically in this paper. Several studies have shown that TFS information is important for speech perception, especially in a noisy background (Hopkins and Moore, 2009;Hopkins et al, 2008) although a recent study has questioned this (Apoux and Healy, 2013). In view of the important role of TFS in speech recognition and the speech perception problems in SNHL participants in noisy conditions, it has been assumed that TFS perception problems may exist in SNHL participants (Gnansia et al, 2009;Moore, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…The relative independence with which various timefrequency (T-F) units of speech may be processed is relevant to the glimpsing model of speech perception in noise (Cooke, 2006;Apoux and Healy, 2013) and to binarymasking techniques used to separate speech from noise (e.g., Wang, 2005). In the glimpsing model, the auditory system bases the speech percept on T-F units containing relatively clean speech and essentially disregards T-F units dominated by noise.…”
Section: Introductionmentioning
confidence: 99%